2012
DOI: 10.1364/josab.29.000513
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the hyperpolarizability poorly determines the potential

Abstract: We have optimized the zero frequency first hyperpolarizability β of a one-dimensional piecewise linear potential well containing a single electron by adjusting the shape of that potential. With increasing numbers of parameters in the potential, the maximized hyperpolarizability converges quickly to 0.708951 of the proven upper bound. The Hessian of β at the maximum has in each case only two large eigenvalues; the other eigenvalues diminish seemingly exponentially quickly, demonstrating a very wide range of nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 15 publications
4
44
0
Order By: Relevance
“…Monte Carlo simulations discovered the optimum energy spectrum for such molecules and provided a strong indicator of the origin of the gap [7]. Optimization of the effective potential energy an electron experiences across the main direction of a quasi-linear molecule showed that the hyperpolarizabilities may be increased by tuning a few parameters [8], by modulation of conjugation along a chain [9], or by donor-acceptor substitution and insertion of spacers [10]. However, there is no general rule about how to construct the ideal potential energy profile across a molecule to maximize the nonlinear optical response.…”
mentioning
confidence: 99%
“…Monte Carlo simulations discovered the optimum energy spectrum for such molecules and provided a strong indicator of the origin of the gap [7]. Optimization of the effective potential energy an electron experiences across the main direction of a quasi-linear molecule showed that the hyperpolarizabilities may be increased by tuning a few parameters [8], by modulation of conjugation along a chain [9], or by donor-acceptor substitution and insertion of spacers [10]. However, there is no general rule about how to construct the ideal potential energy profile across a molecule to maximize the nonlinear optical response.…”
mentioning
confidence: 99%
“…The energy difference between the ground and first excited state, E 10 , sets a fundamental limit on the electric polarizability and first hyperpolarizability. These limits have been corroborated by experiment [12], potential optimization [13][14][15][16][17], and calculations on quantum graphs [18][19][20][21] though a recent Monte Carlo study utilizing filtered sampling suggests that these limits may be an overestimate by approximately 30% [22].…”
Section: Introductionmentioning
confidence: 84%
“…In fact, the g = −5 curve seems to rise to its maximum as the delta moves from the left edge, but then it drops to a lower value, rather than increasing and perhaps exceeding the 0.71 limit. This effect appears to be related to the universal result that all graphs whose β are calculated by starting with a Hamiltonian and a potential of any kind have β xxx ≤ 0.7089, the potential optimization limit 29,33 . The sum rules do not constrain β xxx from equaling unity, as has been shown in a Monte Carlo calculation that starts with the energies and transition moments (top-down), rather than with a Hamiltonian and its energies and states (bottom-up) 52 .…”
Section: The Compressed Delta Atommentioning
confidence: 98%
“…Recent examination of the origin of the limits has suggested that the true limits are indeed those from potential optimization and not those determined solely by the sum rules 32 . Corroborating results have also been provided 33 , but have shown that optimization poorly determines the potential.…”
Section: Introductionmentioning
confidence: 99%